PERILAKU KOLOM KOMPOSIT TABUNG BAJA BERISI BETON NORMAL AKIBAT BEBAN AKSIAL SENTRIS DAN EKSENTRIS - Desi Putri (Sekolah Tinggi Teknik - PLN, 2016)
The columns are an important part of the structure.Column continued load from of plate and beams untilto foundation.The column is a structural component that is dominant receiving axial loads. Composite columnin this review is a steel column which is made from tube or steel pipe and filled with structural concrete. Thisresearch is carried out to understand the properties of the behavior of composite columns of normal concretecasted in cylinder steel tube; to understand the effect of variations of the slenderness ratio of the loaddeflectionand strength correlations as well as understanding failure behavior of normal concreted steel tubecomposite columns with a variation of the eccentric loads. The preparation of the test specimen is based onthe variation of the ratio of tube thickness (D/t), the slenderness ratio (L/D), and the Eccentric ratio (e/D).Test specimen consists of 15 columns of concrete core, 15 steel pipe columns, 21 composite columns ofnormal centric concreted steel pipe and 18 composite columns of normal eccentric concreted steel pipe whichthen loaded centric axial and eccentric.The results show that the capacity of the composite columns is overallhigher about 7%-26% rather than the algebraic sum of the capacity of its components (steel tube and coreconcrete). The pattern collapse composite columns of normal concreted steel pipe due to centric and eccentricloads showed shear failure and axial and is local. But for the eccentric column is only one side of the crosssectionand only the tube steel buckle comes together with the concrete core suffered spall at the samelocation.